2014
DOI: 10.1515/prilozi-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Genotype Variability and Haplotype Profile of Abcb1 (Mdr1) Gene Polymorphisms in Macedonian Population

Abstract: The aim of this study was to evaluate the most common ABCB1 (MDR1, P-glycoprotein) polymorphisms in the population of R. Macedonia and compare the allele and haplotype frequencies with the global geographic data reported from different ethnic populations. The total of 107 healthy Macedonian individuals from the general population was included. Genotypes for the ABCB1 for three polymorphisms C1236T [rs1128503], G2677A/T [rs2032582] and C3435T [rs1045642] were analyzed by Real-Time PCR. Obtained allele frequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 75 publications
1
7
1
Order By: Relevance
“…For example, in our study 1236C allele had a frequency of 51.6 % in healthy population, same results being reported in Macedonians (56%), Serbians (53%), Germans and Hungarians (55%) but not in a gipsy (44%) and Slovenians (39%) [32][33][34]. 2677G allele frequency in our study was found in 51% of patients, similar to other European populations (from 53 to 56%).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For example, in our study 1236C allele had a frequency of 51.6 % in healthy population, same results being reported in Macedonians (56%), Serbians (53%), Germans and Hungarians (55%) but not in a gipsy (44%) and Slovenians (39%) [32][33][34]. 2677G allele frequency in our study was found in 51% of patients, similar to other European populations (from 53 to 56%).…”
Section: Discussionsupporting
confidence: 90%
“…[37,38] A strong association for C1236T and G2677T linkage disequilibrium was observed in a Macedonian study. [32] When we analysed the linkage between these two SNPs the most frequent genotype we found was CT/GT, followed by CC/GG and TT/TT, but no statistical differences were detected between the study groups or associated with drug-resistant epilepsy. In a study conducted in Romania, using a group of 70 epileptic children with idiopathic and symptomatic epilepsy, in which three MDR1 polymorphisms (C3435T, G2677T and C129T) were monitored, Buzoianu et al did not succeeded demonstrate association of these polymorphisms to drug resistant epilepsy, even after patients on monoterapy selection.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Our data showed similar allele and genotype distributions of 1236C>T, 2677G>T/A SNPs with the general frequencies reported in European Caucasians [10,28,29] but different from those described in Asian populations including Japanese [30,31], Chinese, and Indian [32,33,34]. The allele and genotype distributions of 3435C>T SNP were compatible to those reported in Asian studies [30,31,32,33,34], while they differed from those described in European [10,28,29], African American, and Sub-Saharan African populations [35]. …”
Section: Discussioncontrasting
confidence: 53%
“…For the analyses of the rs1045642 SNP of the ABCB1 gene, and the rs4149056 and rs4149014 SNPs of the SLCO1B1 gene, substantial heterogeneity was observed; this may be due the variable frequencies of genotypes across different geographical areas. Indeed, allele frequencies have been found to vary considerably between different ethnic populations for the rs1045642 SNP (61), for the rs4149056 SNP (also known as SLCO1B1 521T-C) (62) and the rs4149014 SNP (63).…”
Section: Resultsmentioning
confidence: 99%